Light Side Coupling on ZnO Nanorods-Coated Glass Substrate for Lactose Sensing - Jahava, Marlina; Jali, Mohd Haviz; Johari, Md. Ashadi Md.; Norashikin, Mohd Adili; Yusof, Haziezol Helmi Mohd; Ahmad, Aminah (Engineering, Technology & Applied Science Research, 2025)
This study presents a novel sensing device for lactose detection, using ZnO nanorods on glass substrate with a light side coupling technique, as this integration enhances light scattering and adsorption, improving sensing performance. The proposed sensor was exposed to ranging lactose concentrations (0% to 100%) to validate its performance. The results were compared with a classic single light source technique to evaluate several parameters, such as sensitivity, linearity, repeatability, stability, response time, and hysteresis. Τhe experimental findings exhibited a higher sensitivity of 0.0201 V/% concentration, superior linearity of 99.61%, and improved resolution by a factor of 1.5 compared to traditional methods. Due to its cost-effectiveness, simple fabrication process, and superior performance, this sensing platform presents a viable alternative for industrial optical sensing applications, particularly in food quality monitoring and biomedical diagnostics.